Restoration of eroded coastal sand dunes using plant and soil-conditioner mixture. (September 2016) - Hong, Sun Hwa; Lee, Eun Young
Abstract: In this study, we evaluated the ability of a soil-conditioner mixture to reduce soil erosion of coastal sand dunes. Plant growth-promoting rhizobacterium Bacillus sp. SH1RP8 was isolated from indigenous plants normally found in coastal sand dunes. Potassium polyacrylate, a superabsorbent polymer, was applied as a soil-conditioner to evaluate the promotion of Arundo donax growth in sand dunes at Songjeong beach (site A) and Soongut beach (site B), South Korea. This soil-conditioner mixture increased the shoot length of A. donax cultivated for 10 months at both the sites, specifically 167.52% at site A and 122.78% at site B, whereas shoot biomass increased by 370.64% and 149.30%, respectively. The viable cell count of strain SH1RP8 was maintained during the vegetation restoration period. Soil containing A. donax lost soil at a rate of 1.61% when it was watered daily for 8 days (2 L/day), whereas the loss was 55% in the control plots. These results indicate that the soil-conditioner mixture containing SH1RP8 can serve as a promising microbial inoculant for increasing plant growth in coastal sand dune environments, and for improving the phytostabilization efficiency and preventing soil erosion. Highlights: Effective use of a soil-conditioner mixture to reduce erosion in costal sand dunes. Enhancing growth of Arundo donax to preserve costal sand dunes. Microbial inoculant increases plant growth in coastal sand dunes. Application of soil-conditioner mixture in situ at a field study site in Korea.